HUBUNGAN PENGETAHUAN IBU DAN DUKUNGAN SUAMI DENGAN PENGGUNAAN KONTRASEPSI INTRA UTERIN DEVICE - Turiyani, Turiyani (JURNAL KESEHATAN TERAPAN, 2021)
The family planning program is not only aimed at controlling the rate of population growth, but also to meet the community's demands for quality family planning and reproductive health (KR) services, in accordance with the maternal mortality rate (MMR) and infant mortality rate (IMR). ) as well as overcoming reproductive health problems to form quality small families. Objective: to determine the relationship between mother's knowledge and husband's support with the use of Intra Uterine Device contraceptives. Methods: The type of research used in this study used the Analytical Survey method with a Cross Sectional approach where data on the independent variable (husband's knowledge and support) and the dependent variable (IUD use) were measured and collected at the same time (Point Time Sample Approach in this study). is a sampling technique used with Non Random Sampling (not random), namely accidental sampling where the sample is taken based on considerations that focus on certain goals (due to certain characteristics or characteristics considerations) totaling 76 people. Result: The results show that there is a relationship between knowledge pregnant women (p-value 0.0039, p<0.05) and there is a relationship between husband's support (p-value 0.016, p<0.05) Conclusion: There is a relationship between mother's knowledge and husband's support with the use of intra uterine contraceptives (IUDs). Keywords: Knowledge, Husband's Support, IUD Contraceptio